Memahami Analisis Pekerjaan Sebagai Dasar Perencanaan Sumber Daya Insani - Lingkan Agnes Safitri; Valenzchi Yufancua; Sunarti Sunarti (Pusat Riset dan Inovasi Nasional, 2024)
Job analysis is the key to planning human resources effectively. This involves a deep understanding of the duties, qualifications, and responsibilities of a job. With proper analysis, organizations can plan recruitment, selection, development and assessment of employees in accordance with the needs of the position. It also helps ensure employee-job match, increases productivity, and achieves organizational goals. In the context of human resource planning, job analysis is the foundation that enables efficient and strategic workforce management